Efforts to Reform State Civil Apparatus Management in the Face of Globalization - Beltahmamero Simamora (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Currently, Indonesia's institutional structure is overweight with 34 ministries, 28 non-ministerial government institutions, and around 69 non-structural institutions with overlapping authority, indicating the complexity of government fragmentation in Indonesia. Globalization will intervene more in the field of government institutional restructuring when Indonesia's institutional situation is too hierarchical, fragmented, and over-procedural. This paper aims to discuss the importance of ASN management and how the government steps to actualize public values in ASN reform. This research uses a qualitative approach, which describes the efforts to reform ASN management in the face of globalization. The data collection technique used in this research is a literature study by collecting materials from books, journals, by describing the data through several experts' opinions. This paper proposes a recommendation that institutional downsizing is a logical consequence of the fragmented condition of Indonesian government institutions, the president should dare to reorganize the power structure in order to save the cost of governance. The quality of ASN in the face of globalization should be strengthened by recruiting younger employees who understand the dynamics of technological development, and educating ASN personnel by conducting special trainings in responding to globalization as a challenge that must be faced.